Congenital Syphilis : Still a Reality in Bangladesh - Das, Dhananjoy; Akter, Wahida; Uddin, Mohammad Ohi; Ahmed, Rehana; Arzu, Mahmood A Chowdhury (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Congenital syphilis is caused by Treponema Pallidum. The fetus can acquire it transplacentally during maternal spirochetemia, or contact with genital lesion during the intrapartum period. The prevention and treatment of congenital syphilis are very much cost-effective, but if it remains undiagnosed and untreated, can result in a deadly outcome. It can affect multiple organs and systems. In this present case, skeletal systems were predominantly involved. The clinical presentation was the failure to gain weight, painful mobilization of the right arm, and swelling of the proximal and distal end of this arm. Erythematous, maculopapular scaly skin eruption was also noticed in the scalp and scrotum. Radiological examination showed metaphyseal irregularity, and periosteal reaction at the right humerus, radius, and ulna. Nontreponemal antibody test (VDRL) and a treponemal antibody test (TPHA) both were reactive. Early congenital syphilis may have a subtle clinical presentation or may remain asymptomatic. Therefore physicians should aware of the clinical presentation of congenital syphilis; at the same time, detailed clinical history can play an important role to suspect congenital syphilis. Promotion of pregnant women for antenatal care and screening for syphilis in the first trimester are the keys to eliminating congenital syphilis. Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 73-77